Effect of phosphate on frozen Nile tilapia fillets - Wangtueai, Sutee; Tongsiri, Sudaporn; Maneerote, Jirawan; Supaviriyakorn, Wuttipot (Food and Applied Bioscience Journal, 2017)
The yield and quality of frozen Nile tilapia fillets treated with various individual phosphates including sodium acid pyrophosphate (SAPP), tetrasodium pyrophosphate (TSPP), sodium tripolyphosphate (STPP), sodium hexametaphosphate (SHMP), and different mixed phosphates at 2.0% concentration in the presence of 2.5% NaCl were studied. The 2% STPP gave the greatest weight gain and cooking yield with the least drip loss and cooking loss as well as slightly enhancing the sensory acceptability score of the fillets. The actual phosphate content in the fish fillets never exceeded the European standard of 5 g/kg sample.